The Relationship between Personality Traits and Academic Motivation in Nursing Student - Moghimian M; Karimi T (Iran University of Medical Sciences, 2012)
Background & Aims: Academic motivation plays an important role in acquiring knowledge and skills. The role of personality in educational success is beyond intelligence. The aim of this study was to investigate the relationship between personality traits and academic motivation in nursing students.   Material & Methods: It was a descriptive- correlational study. The sample consisted of 250 undergraduate nursing students in Najafabad branch of Azad University who were recruited during 2010-2011 academic year by census. Data related to personality traits and academic motivation was collected by the Persian version of Neo Big Five Inventory (NEO-BFI) and Hurter's Academic Motivation Questionnaire respectively and analyzed by SPSS-PC (v.16) using stepwise regression.   Results: there was a direct significant correlation between academic motivation and conscientiousness trait (P=0.000, r= 0.234) and also extroversion trait (P= 0.001, r= 0.202). There was an inverse significant correlation between academic motivation and neuroticism trait (P= 0.000, r= - 0.219).no significant relationship was seen between academic motivation and openness and agreeableness traits. Conclusion: this study showed that some Personality traits explain academic motivation in nursing students. Therefore it is suggested that those involved in teaching nursing students consider the role of personality traits when recruiting this students in nursing schools